Two new Neotropical species of Perithreticus Vaillant 1973 (Diptera: Psychodidae, Psychodinae). (3rd May 2016) - Kvifte, Gunnar Mikalsen; Andersen, Trond; Hagenlund, Linn Katrine; Bello González, Orestes C.
ABSTRACT: The genus Perithreticus is recorded for the first time from Central America and the Caribbean. Two new species are described and figured: P. arboscandens Kvifte & Andersen, n. sp. from Zurquí, San José Province, Costa Rica and P. guantanamera Kvifte & Andersen, n. sp. from Alexander von Humboldt National Park, Guantánamo Province, Cuba. The generic diagnosis is emended to accommodate the newly described species, and a key to the males of the Perithreticus species of the world is presented.